FULL TABLET AND HALF TABLET EMPAGLIFLOZIN PRESCRIPTION DEMOGRAPHIC AND GLYCEMIC CONTROL: A SINGLE CENTRE EXPERIENCE - Keong, See Chee; Jasmiad, Nurbadriah; Ismail, Ilham; Eileen, Tan; Yeong, Ong Poh; Lan, Wong Zhe (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION Sodium-glucose co-transporter 2 (SGLT2) inhibitors prescription has been given greater emphasis in recent years, and it has been adopted as a first-line or secondline treatment in major international guidelines. In the public practice of the Ministry of Health hospital, the main SGLT2 inhibitor prescribed is empagliflozin. However, the prescription is still limited by cost despite efforts to increase prescription. The practice of prescribing half tablet empagliflozin (12.5 mg) has yet to be recommended but has been widely practiced in many centres in Malaysia. There is no evidence advising for or against this practice. Hospital Sultan Haji Ahmad Shah (HoSHAS), a tertiary hospital in Central Pahang, has initiated a prescription of half a tablet of empagliflozin (12.5 mg) in 2019. An assessment of this empagliflozin prescription pattern and its effects on glycemic control is essential to inform future prescription direction. METHODOLOGY This cross-sectional study was conducted in HoSHAS, a tertiary hospital in Temerloh, Pahang, Malaysia, in March 2023. All patients on treatment were included in the study. Electronic medical records were reviewed for patient demographic data and glycemic control at initiation, and the latest follow-up data were collected. The study aimed to determine the demographic profile of patients on empagliflozin and the difference in glycemic control between full-tablet empagliflozin (25 mg) and half-tablet empagliflozin (12.5 mg) in this cohort. RESULTS There were 167 patients on empagliflozin, which reflected a three-fold increase compared to 2021. The majority of patients (83%) were on half-tablet empagliflozin. The median age of patients was 54 (IQR: 44-63). Most were male (62.9%) and of Malay ethnicity (76.6%). In this cohort, 21.6% had a prior myocardial infarction, 10.8% with congestive heart failure, 22.2% with obesity, 73.7% with hypertension, and 46.7% with dyslipidemia. 23.4% of patients had diabetic retinopathy, while 19.2% had incident nephropathy. 57.5% and 38.9% of patients on empagliflozin were on concomitant insulin therapy and sulphonylurea, respectively. At the latest follow-up, 51.5% of patients had HbA1c below 8.5% with a mean HbA1c of 8.65 (SD = 1.9). There was no statistical difference in mean HbA1c reduction from initiation to latest follow up in the group on full-tablet and half-tablet empagliflozin 1.48% vs - 1.65%, p >0.05). CONCLUSION The use of SGLT2 inhibitors must be maximized further to provide cardio-renal and metabolic benefits to high-risk type 2 diabetes patients while balancing costs. This study demonstrated that the prescription of whole or half tablets did not cause differences in glycemic control. Therefore, such practice can be adopted, but further studies on the long-term effects of the dose on cardio-renal and metabolic outcomes need to be explored.